Study on Financial Crises in an African Open Economy - Oluremi Ogun; Olutomilola Makinde (Modern Perspectives in Economics, Business and Management Vol. 2, 2021)
This study looked into the possible reasons of crises in Nigeria’s financial sector from 1960 to 2014. The scope of the study encompassed two distinct phases of the country’s financial crises. Both the country’s policy and economic environments might have played a significant role in the magnitude of the crises experienced during the various periods. The empirical model was defined by an analytical approach embedded in allied studies. Preliminary analyzes were conducted on the data used to rule out the possibility of spurious statistical results. Both endogenous and exogenous components were estimated using a regression model. The majority of endogenous factors had extremely consistent signals and importance. The impact of most exogenous causes and closely related domestic activity found parallels in the country’s business cycles. Greater caution in policy design and a lower propensity to borrow externally could help to mitigate the negative effects on the system’s growth determinants.